Internationalizing Sub-Saharan Africa’s Education and Health Services - Dihel, Nora Carina; Goswami, Arti Grover (World Bank, Washington, DC, 2015)
This paper summarizes the nature and determinants of trade in education and health services in a selected group of countries in Eastern and Southern Africa, using a combination of quantitative and qualitative methods. The paper presents results from new, innovative data collection methods, such as crowdsourcing, to shed some light on the magnitude, determinants, and restrictions on intra-African trade in education and health services. Assessments of trade and regulatory barriers, based on results from regulatory surveys conducted in selected East African countries, and case studies of success stories and less favorable experiences are then used to develop policy recommendations for using trade and regional integration more strategically to improve outcomes in education and health. The analysis shows that to turn these sectors around, policy action is required in the areas of education, domestic regulation, trade policy, labor mobility, and information and communications technologies at the national and international levels. To retain some of the scarce health workers in the region and enhance the region’s competitiveness in providing education and health services, African countries should allow for freer mobility of teachers and health care professionals.